The burden of surgical site infection and associated factors among patients admitted to the surgical ward in resource-limited countries: an institutional-based cross-sectional study - Zewdu, Simachew; Daniel, Abel; Abebe, Amene; Abraham, Zinabu; Elias, Hailu; Belete, Adamu (Frontiers in Surgery, 2025)
BackgroundSurgical site infections (SSIs) are a leading cause of morbidity and mortality worldwide. Particularly, in low- and middle-income countries (LMICs), they are the most prevalent kind of healthcare-associated infection (HAI), and they play a role in the emergence of antibiotic resistance, which can result in serious illnesses. Therefore, this study aims to ascertain the burden and association of surgical site infection among patients on the surgical ward in resource-limited surgical setups.MethodAn institutional-based cross-sectional study was conducted in Wolaita Sodo University Comprehensive Specialized Hospital from March 1, 2022 to July 30, 2023. A systematic random sampling method was employed. Data management and statistical analysis were performed using SPSS version 25. An adjusted odds ratio (AOR) with 95% confidence interval was used to measure the association between dependent and independent variables. A p-value < 0.05 was used to determine the level of significance.ResultThis study included a total of 309 patients, of whom 198 (64.1%) were males. The average age of the participants was 42, and participants more than 42 years’ old totaled 156 (50.5%); the type of residence was found to be rural for 236 patients (84.6%). The magnitude of surgical site infection was calculated to be 29.1%. Predisposing factors for surgical site infection included male sex (AOR −4.9; 95%; 2.0–11.3), drainage use (AOR −4.46; 95%; 1.9–10.3), and abdominal surgery (AOR−4.3; 95%; 1.3–14.1), whereas protective factors included younger female sex, elective surgery, and a surgery duration of less than 2 h.